2022
DOI: 10.53730/ijhs.v6ns8.13168
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for genitourinary infection in individuals with type 2 diabetes using SGLT2 inhibitors

Abstract: Aim: To assess the frequency and risk factors for genitourinary infections in people with type 2 diabetes who are using SGLT2 inhibitors. Study design: A retrospective study. Place and Duration: Jinnah Hospital Lahore from March 2021 to March 2022. Methodology: This study included 57 people with type 2 diabetes who were using SGLT2 inhibitors.The parameters linked to genitourinary infections were observed via the use of multiple logistic regression analyses. This study utilized patients' medical records for ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…According to their findings, individuals who had been using the medicine for four months had a greater rate of UTIs. They also observed that the link between UTIs and female gender was strong [26].…”
Section: Discussionmentioning
confidence: 97%
“…According to their findings, individuals who had been using the medicine for four months had a greater rate of UTIs. They also observed that the link between UTIs and female gender was strong [26].…”
Section: Discussionmentioning
confidence: 97%